The angered versus the endangered: PCCs, roads policing and the challenges of assessing and representing ‘public opinion’ - Wells, Helen (The British journal of criminology, 2018)
Part of the rationale for introducing elected Police and Crime Commissioners (PCCs) was a suggestion that the police and public needed to be ‘reconnected’, with the public more readily able to shape the type of policing they wished to receive. Apparently underpinning this intention was a perception that a single public view about policing priorities could, and would, make itself apparent to PCCs. This paper considers how PCCs assess their public mandate by focusing on an often contested policing activity—roads policing. It considers why this particular issue is particularly likely to be understood by PCCs as a contested topic and, furthermore, how PCCs go about accessing and representing diverse views within this ‘consumer-led’ approach to the provision of policing.